2013
DOI: 10.1111/mec.12450
|View full text |Cite
|
Sign up to set email alerts
|

Carving out turf in a biodiversity hotspot: multiple, previously unrecognized shrew species co‐occur onJavaIsland,Indonesia

Abstract: In theory, competition among species in a shared habitat results in niche separation. In the case of small recondite mammals such as shrews, little is known about their autecologies, leaving open questions regarding the degree to which closely related species co-occur and how or whether ecological niches are partitioned. The extent to which species are able to coexist may depend on the degree to which they exploit different features of their habitat, which may in turn influence our ability to recognize them as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 80 publications
1
41
0
Order By: Relevance
“…While the addition of > 300 species each of rodents and bats is unsurprising given their existing diversity, these clades may reasonably contain disproportionally high levels of cryptic diversity (e.g., Ruedi and Mayer 2001;Belfiore et al 2008), and thus the application of genetic sequence data may continue to yield greater insights. Within Eulipotyphla (most particularly in shrews), we expect that the discovery of new species will continue given their rate of recent discoveries and frequency of morphological crypsis (Esselstyn et al 2013). The species richness in Sorex (86 species) and Crocidura (197 species) suggests that genus-level revisions are needed and, when conducted, are likely to yield further taxonomic rearrangements (Castiglia et al 2017;Matson and Ordóñez-Garza 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While the addition of > 300 species each of rodents and bats is unsurprising given their existing diversity, these clades may reasonably contain disproportionally high levels of cryptic diversity (e.g., Ruedi and Mayer 2001;Belfiore et al 2008), and thus the application of genetic sequence data may continue to yield greater insights. Within Eulipotyphla (most particularly in shrews), we expect that the discovery of new species will continue given their rate of recent discoveries and frequency of morphological crypsis (Esselstyn et al 2013). The species richness in Sorex (86 species) and Crocidura (197 species) suggests that genus-level revisions are needed and, when conducted, are likely to yield further taxonomic rearrangements (Castiglia et al 2017;Matson and Ordóñez-Garza 2017).…”
Section: Discussionmentioning
confidence: 99%
“…; Brown & Siler ; Esselstyn et al . ). Thus, it is notable that this study has revealed predicted patterns of genetic variability in which, despite the species’ presence in virtually all terrestrial habitats of South‐East Asia, the genetic signal of landscape fragmentation and oceanic barriers to gene flow are detectable at a finer genomic level.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, our failure to detect isolation by environment along with the observed low population structure makes sense given the wide geographical range and apparent generalist ecological preferences exhibited by this species. Interestingly, in several recent mainland versus adjacent island archipelago comparisons of genetic diversity of widespread vertebrates, the expectation of a genetically homogenous continental population as compared to more genetically structured or fragmented island archipelago populations has not been observed (Stuart et al 2006;Brown et al 2010;Esselstyn et al 2013). Thus, it is notable that this study has revealed predicted patterns of genetic variability in which, despite the species' presence in virtually all terrestrial habitats of South-East Asia, the genetic signal of landscape fragmentation and oceanic barriers to gene flow are detectable at a finer genomic level.…”
Section: Biogeographical Expectationsmentioning
confidence: 99%
“…Laboratory protocols followed those of Esselstyn et al . (, ). We first sequenced 684 bp from the 3′ end of cytochrome b (CytB) in 267 specimens ().…”
Section: Methodsmentioning
confidence: 97%
“…We extracted, amplified and sequenced various fragments of DNA from montane populations of the Crocidura monax species complex and several potentially related taxa. Laboratory protocols followed those of Esselstyn et al (2009Esselstyn et al ( , 2013. We first sequenced 684 bp from the 3′ end of cytochrome b (CytB) in 267 specimens (Appendix).…”
Section: Dna Sequencing and Analysismentioning
confidence: 99%